Optimization of immunosuppressive therapy during the third kidney transplant in the early postoperative period. Clinical observation - O. N. Rzhevskaya; A. V. Pinchuk; E. I. Pervakova; A. V. Babkina (Бюллетень сибирской медицины)
The choice of immunosuppressive therapy is determined by the degree of sensitization to the histocompatibility gene complex on chromosome 6 (HLA). The risk of rejection in the early periods after surgery  increases for the patients with repeated kidney transplantation. Optimizing immunosuppressive therapy is the only  way to prolong the life of a patient with a terminal stage of chronic renal failure. имости на 6-й хромосоме (НLA). The analysis of a clinical case of a 47-year-old patient who was undergoing treatment at the N.V. Sklifosovsky Scientific Research Institute of Emergency Medicine after the third allotransplantation of a cadaveric kidney in 2016 was performed. The patient was diagnosed with chronic glomerulonephritis (IgA-nephropathy) chronic end-stage renal failure; in the early postoperative period, in addition to basic immunosuppression, anti-lymphocytic polyclonal antibodies were prescribed in combination with plasmapheresis sessions for the treatment and prevention of acute rejection crisis in the early postoperative period. For the first time, in order to prevent the development of an acute rejection crisis and minimize infectious complications of immunosuppressive therapy in the recipient after the third kidney transplant, plasmapheresis sessions were used using a plasmapheresis filter with a polymethylacrylate membrane in combination with a short course of polyclonal antibodies.